Function of Alpha-Lipoic Acid in Rabbits as An Antioxidant and to Lower Lipid Levels - Laila Alfageih,; Ahlam Amharib,; Fayrouz Khaled,; Fatma Auad, (AlQalam Journal of Medical and Applied Sciences, 2024)
As a thiol-replenishing and redox-modulating agent in cells, Alpha lipoic acid ‘ALA—also known as 'thioctic acid, 1,2-dithiolane-3-pentanoic acid, 1,2dithiolane-3-valeric acid, or 6,8-thioctic acid—has attracted a lot of medicinal interest. Naturally, alpha lipoic acid is needed as a cofactor for the oxidative decarboxylation responses of the glucose digesting system to lose life. Thus, the goal of this investigation was to draw attention to how thioctic acid affects lipid profile. Critical papers were found by a deliberate search of PubMed/Medline, Scopus, Web of Science, Cochrane Library, and Embase through October 2023. The rabbits were given an oral dose of 60 mg/kg BW of thioctic acid. Rabbits were given the tried measurements daily for a period of 12 weeks. The results demonstrated that thioctic acid caused a critical (PB/0.05) decrease in the levels of glucose, "TBARS", "cholesterol", triglycerides "TG", low density lipoprotein "LDL", and very low-density lipoprotein "VLDL", while the level of high-density lipoprotein "HDL" increased in comparison to the control group. يهدف هذا البحث إلى دراسة دور حمض ألفا ليبويك كمضاد للأكسدة وخافض للدهون في الأرانب. حمض ألفا ليبويك هو مركب كيميائي يتميز بخصائصه الفريدة كمضاد للأكسدة وقدرته على تعديل مستويات الدهون في الجسم. تم إجراء البحث على مجموعة من الأرانب التي تلقت جرعات يومية من حمض ألفا ليبويك بجرعة 60 ملغ/كغ من وزن الجسم لمدة 12 أسبوعًا. أظهرت النتائج أن حمض ألفا ليبويك أدى إلى انخفاض كبير في مستويات الجلوكوز، والـTBARS (مؤشر للإجهاد التأكسدي)، والكوليسترول، والدهون الثلاثية، والبروتين الدهني منخفض الكثافة، والبروتين الدهني منخفض الكثافة جدًا في الأرانب مقارنة بالمجموعة الضابطة. في المقابل، شهدت مستويات البروتين الدهني عالي الكثافة ارتفاعًا ملحوظًا. تشير هذه النتائج إلى أن حمض ألفا ليبويك يمتلك خصائص مضادة للأكسدة وقدرات فعالة في تحسين ملف الدهون في الجسم، مما يجعله مرشحًا محتملاً للاستخدام في الوقاية والعلاج من اضطرابات الدهون والأمراض المرتبطة بالإجهاد التأكسدي